Extension of dual equivalent linearization technique to flutter analysis of two dimensional nonlinear airfoils - Triet, Nguyen Minh (Vietnam Journal of Mechanics, 2015)
This paper extends the dual equivalent linearization  technique (ELT) to obtain flutter speeds of a two-dimensional airfoil  with nonlinear stiffness and damping in pitch degree of freedom.  Although the use of dual ELT has been investigated in some previous papers,  this paper presents an extension of dual ELT using the global-local  approach, in which the local equivalent linearization coefficients are averaged in the  global sense. The numerical calculation shows that the extended dual ELT  gives more accurate flutter speeds in comparison with the ones of classical  ELT.